DFT Studies of Indium Nanoclusters, Nanotubes and their Interaction with Molecular Hydrogen - Hussain, A.; Baig, M. W.; Mustafa, N. (The Nucleus, 2015)
Density functional theory calculations have been performed on Indium nanoclusters (Inn, n= 3 to 10) to explore the relative stability among their different isomers and interaction with H2. Geometry optimizations starting from initial candidate geometries were performed for each cluster size, so as to determine a few low energy isomers for each size. Clusters with planar configuration and high symmetry are found to be more stable. For n=8, there comes transition from 2D to 3D structures. Energetically favorable isomers of indium nanoclusters for each size were considered to get H2 adsorbed. In general H2 interaction with these clusters is weak but with those comprising of some odd number of atoms i.e. 5, 7 and 9 is considerable. Indium nanotube also indicates H2 adsorption but Eads increases many folds on introduction of defect in the tube. On the basis of DFT investigations, it is suggested that apparently indium nanoclusters and tubes of specific size seem better candidates for materials to store hydrogen.